Expanding Small Pore Size of the Bimodal Catalyst with Surfactant and Its Application in Slurry–phase Fischer‐Tropsch Synthesis. Issue 4 (9th April 2016) - Ishihara, Daisuke; Sun, Jian; Li, Jie; Wei, Qinhong; Tsubaki, Noritatsu
Abstract: The pore size effect on the reaction activity and hydrocarbon selectivities of Fischer‐Tropsch synthesis (FTS) is investigated on the Co‐based bimodal catalysts with tunable small pores and large pores, prepared by employing various surfactants, such as PEG400, PEG600 and P123. The small pore size is enlarged to 4–10 nm, higher than conventional bimodal catalysts prepared by nanoparticles from sol or solution of support precursor. The depth of small pores can also be enlarged by increasing the ZrSiO4 loading amount of the Zr−Si bimodal support, promoting dispersion of cobalt nano‐crystallite. The higher cobalt reduction degree is achieved on these small pore enlarged catalysts, enhancing the activity of FTS. The P123‐assisted one exhibits the highest CO conversion owing to its largest small pore size. The enlarged small pore of 5 nm prepared with PEG400 is the optimized pore size to accelerate the carbon chain growth reaction, producing more heavy hydrocarbons compared to the others. Abstract : Co‐based bimodal catalysts with mesopores of several nanometers and macropores are successfully prepared by loading cobalt nanoparticles on PEG or P123 modified Zr‐Si bimodal support. The pore distribution severely affects FTS activity and hydrocarbon selectivity. The size of small pores is clearly enlarged after the addition of pore‐forming agents, resulting in higher CO conversion and more heavy hydrocarbons in slurry‐phase Fischer‐Tropsch synthesis.